Investigation of general surgery consultations in COVID-19 patients treated in a tertiary hospital - Ulutaş, Mehmet Eşref; Arslan, Kemal (The European Research Journal, 2023)
Objectives: The aim of the study is to reveal the most common general surgery problems during the pandemic period in our center, where all departments only deal with COVID-19 patients. Methods: In our study, general surgery consultations made between 1st November 2020 and 1st February 2021, when our center only served pandemic patients, were retrospectively examined. Demographic data of the patients, distribution of the departments where consultation was requested, reasons for consultation, pathology detection rate, treatment modalities, mortality rates and surgical procedures were included. Results: A total of 70 patients, 33 female, and 37 male, were included in this study. The most common problems of the patients were gastrointestinal system (GIS) problems (46/70, 65.7%). The second most common problem was hepatopancreaticobiliary problems (12/70, 17.1%). This was followed by soft tissue disorders, hernia problems, and trauma cases, respectively. These were mostly treated medically, but surgical treatment was sometimes required (77.1% vs 22.9%). Conclusions: As reported in the literature, the most common surgical pathologies in patients diagnosed with COVID-19 are usually related to the GIS. These pathologies can mostly be treated medically (73.9%). However, surgical treatment was more rarely required (26.1%). The highest rate of surgical treatment was for hernia patients (100%). In general, medical treatment was successful.